Isolation, molecular characterization and phylogenetic analysis of Mycoplasma gallisepticum and Mycoplasma synoviae strains recovered from commercial broiler chicken flocks affected with respiratory tract infections - Jay Prakash Yadav; Yarvendra Singh; Kanisht Batra; Ramesh Kumar; N.K. Mahajan; Naresh Jindal (The Microbe, 2025)
Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS) causes significant economic losses to the poultry industry. The present study was aimed to screen poultry tissue samples (n = 86) collected from dead birds having history of respiratory tract infections, observed while postmortem examination, for the detection of MG and MS and delineating its evolutionary relationships with MG and MS strains circulating in different parts of the globe using phylogenetic analysis. The samples were simultaneously processed for the isolation/culture of pathogen as well as its molecular characterization using PCR assays. In culture, 11.63 % (10/86) tissue samples were found positive for Mollicutes organisms, which were showing typical nipple shaped colonies over Frey’s agar medium. However, in polymerase chain reaction (PCR) assays, using primers for 16S rRNA gene, 41.86 % (36/86), 26.74 % (23/86) and 12.80 % (11/86) samples were found positive for genus Mycoplasma, MG and MS, respectively. The phylogenetic analysis using sequences of intergenic spacer region (IGSR; 16–23S rRNA gene) of MG and vlhA gene of MS leads to grouping of MG and MS isolates of present study and strains of different parts of globes into two clusters. IGSR region of MG and vlhA gene of MS are widely used for evolutionary analysis and differentiation of vaccine and field strains of MG and MS, respectively. The study highlights the status of MG and MS infection in poultry flocks of studied area and its evolutionary relationships with strains circulated in different parts of globe.